2018
DOI: 10.26781/2052-8426-2018-03
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 and RIPK3 - emerging targets in cancer?

Abstract: RIPK1 and RIPK3 are homologous Ser/Thr kinases,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Newton et al reported that the level of NF-kB activation could be induced by TNF in RIPK3-deficient mice [ 30 ]. RIPK3 is thought to be a carcinogenic factor in various cancers, such as breast cancer, intestinal and colon cancer, and lung cancer [ 31 ]. According to our data, RIPK3 expression negatively correlated with prognosis and positively correlated with various tumor-infiltrating lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Newton et al reported that the level of NF-kB activation could be induced by TNF in RIPK3-deficient mice [ 30 ]. RIPK3 is thought to be a carcinogenic factor in various cancers, such as breast cancer, intestinal and colon cancer, and lung cancer [ 31 ]. According to our data, RIPK3 expression negatively correlated with prognosis and positively correlated with various tumor-infiltrating lymphocytes.…”
Section: Discussionmentioning
confidence: 99%